Digital Transformation in Tourism Marketing Governance: Implementation Study in Cibiru Wetan Tourism Village - Mochammad Weka Rifqi Daffa Pangsi; Jaliludin Muslim (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Digital transformation has become a key driver in promoting sustainable tourism development, particularly within village-based destinations that serve as local policy priorities. This study aims to analyze the implementation of digitalization in tourism marketing governance in Cibiru Wetan Tourism Village and its impact on local economic growth and community empowerment. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and document analysis. Data were analyzed using Miles and Huberman’s interactive model. The findings reveal that the use of websites and social media platforms has increased tourist visits, strengthened local economic activities, and encouraged creative community participation. However, challenges remain, including limited digital literacy and institutional capacity. This study highlights the importance of community-based collaborative digital governance for ensuring sustainable tourism development.